2014
DOI: 10.4209/aaqr.2013.02.0041
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chlorinated Aromatic Organic Compounds from MWI with Catalytic Filtration

Abstract: Adsorption with activated carbon and catalytic oxidation with an appropriate catalyst are two methods for the effective removal of gaseous dioxin-like congeners from flue gases. The removal efficiencies of chlorobenzene/chlorophenol (CBz/CPh) from gas streams achieved by an "activated carbon injection + bag filter" (ACI + BF) system in a municipal waste incinerator (MWI) and catalytic filter (CF) system installed in a pilot-scale module are evaluated in this study via sampling and analysis. Real flue gas obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The chloroaromatic it is still the key mechanistic step, in which, some precursors, including CPh, CBz, and PCBs, are formed. Dickson et al 63 added 13 C-PCP to the model fly ash and found that no scrambled PCDD was detected in the de novo process, meaning that the CPh molecule would not react with the carbon matrix to form PCDD. However, Hell et al 73 found that approximately 40% of the total PCDD was formed through condensation of de novo created chlorophenols.…”
Section: Formation Mechanisms Of Pcdd/f In Incinerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The chloroaromatic it is still the key mechanistic step, in which, some precursors, including CPh, CBz, and PCBs, are formed. Dickson et al 63 added 13 C-PCP to the model fly ash and found that no scrambled PCDD was detected in the de novo process, meaning that the CPh molecule would not react with the carbon matrix to form PCDD. However, Hell et al 73 found that approximately 40% of the total PCDD was formed through condensation of de novo created chlorophenols.…”
Section: Formation Mechanisms Of Pcdd/f In Incinerationmentioning
confidence: 99%
“…Before subsequent cleanup processing, 13 C-1,2,3,7,8,9-HxCDD in the alternate recovery stock solution was added for the assessment of purification efficiency. Finally, samples are concentrated and 13 C labeled recovery standard stock solution was added before the analysis by HRGC/HRMS. HRGC/HRMS has been used as the official method for trace analysis of dioxins and can provide accurate measurements for homologues of PCDD/F.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…This technology allows to hold and destroy through catalytic oxidation reaction the PCDD/Fs from solid phase (adsorbed in dust) and gas phase. Hung et al [23] compared the chlorobenzenes and chlorophenols removal efficiencies of catalytic filters and the system composed by the injection of active carbon followed by bag filter. The former was more efficient than the latter, especially as the temperature was increased [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hung et al [23] compared the chlorobenzenes and chlorophenols removal efficiencies of catalytic filters and the system composed by the injection of active carbon followed by bag filter. The former was more efficient than the latter, especially as the temperature was increased [23].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of VOCs has gained widespread attention regarding the air quality in indoor environments (Jia et al, 2008;Parra et al, 2008;Ohura et al, 2009;Pei et al, 2013;Geiss et al, 2014). Several investigators have developed many methods for removing VOCs in the air (Ruddy and Carroll, 1993;Khan and Ghoshal, 2000;Hung et al, 2014). Thermal oxidation has high VOC removal efficiency, but is used only with a high concentration of organic compounds.…”
Section: Introductionmentioning
confidence: 99%